Injury Characteristics of Motorcyclists Involved in Motorcycle Crashes in Klang Valley, Malaysia - Pang, Toh Yen (2000)
The objectives of this study were to establish the relationship between injury outcomes and i) riders' characteristics, ii) their exposure and iii) the motorcycle factors resulting from serious and fatal motorcycle crashes. Data on motorcycle crashes and injuries from January to December 1998 were obtained from two sources, namely the police reports and hospital records. These linked data were then used to examine the injury patterns sustained by the motorcyclists involved in motorcycle crashes in Malaysia. In order to assess the independent variables in influencing the injury outcome, the logistic regression method was used to determine the odds ratios and the multivariate models for the injured motorcyclists. In the statistical analysis, a total of five independent variables were found to significantly (p<O.05) influence the fatality risk. Those variables were (i) age of motorcyclists, (ii) engine capacity of the motorcycles, (iii) objects struck, (iv) type of collisions and (v) location sites. Results showed that fatality risks were likely to associate with older motorcyclists, larger engine motorcycles, collision with a heavy commercial vehicle, head-on collision, and non-junction sites. The study also revealed that the most frequent injuries to fatally injured motorcyclists were head injuries (56.5%) and chest injuries (27.4%). Injuries to the lower limbs, however, accounted for the highest proportion (54.4%) for the serious injury cases investigated. This is followed by the upper limb injuries (19.9%). Most motorcyclists were detained for one or two nights for observation and recovery. The mean stay for all patients were about 5 days. However, those motorcyclists who suffered from lower limb injuries often required longer stay in hospital. In addition, the study indicated that side collisions presented a difficult problem in crash protection towards the lower limbs. Despite the fact that most motorcycles in Malaysia had very little crushable and protective structure around the rider's lower limb region. Whereas, this kind of protection was found to reduce the risk of lower limb injures i n many studies. As such, further investigation on the design of effective leg protector for motorcyclists should be carried out.